2005
DOI: 10.1007/s10886-005-4253-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chemical Defenses among Freshwater Plants

Abstract: Although macrophyte herbivore interactions in freshwater systems were generally disregarded for many years, recent data suggest that herbivory can be intense and important in structuring freshwater communities. This has led to the hypothesis that chemical defenses should be common among freshwater plants, but few studies have reported such chemical defenses, and no previous studies have assessed the frequency of chemical defenses among a substantial number of freshwater plant species. In a study of 21 macrophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 28 publications
1
24
0
1
Order By: Relevance
“…Not many studies have yet investigated chemical defenses in submerged freshwater angiosperms. Many studies have focused on marine macroalgae (Hay 1996;Paul et al 2006) and emergent or floating-leaved freshwater angiosperms Dorn et al 2001;Kubanek et al 2001;Prusak et al 2005). These studies often used omnivorous crustaceans as grazers, against which extracts of submersed species have turned out to be inactive Prusak et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not many studies have yet investigated chemical defenses in submerged freshwater angiosperms. Many studies have focused on marine macroalgae (Hay 1996;Paul et al 2006) and emergent or floating-leaved freshwater angiosperms Dorn et al 2001;Kubanek et al 2001;Prusak et al 2005). These studies often used omnivorous crustaceans as grazers, against which extracts of submersed species have turned out to be inactive Prusak et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have focused on marine macroalgae (Hay 1996;Paul et al 2006) and emergent or floating-leaved freshwater angiosperms Dorn et al 2001;Kubanek et al 2001;Prusak et al 2005). These studies often used omnivorous crustaceans as grazers, against which extracts of submersed species have turned out to be inactive Prusak et al 2005). In contrast, other authors have suggested chemical defenses in submerged freshwater macrophytes against planktivorous Daphnia, lepidoptera, and gastropod herbivores based on observed effects and correlations between secondary plant metabolites and feeding activity or changes in behavior (Pennak 1973;Burks et al 2000;Choi et al 2002;Cohen et al 2002;Elger and Lemoine 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Defense and resistance mechanisms against herbivores have been poorly understood in freshwater; even so we now know that freshwater plants are frequently chemically or structurally defended from consumers [29][30][31]. Structural defenses are more commonly found among upland plants than wetland plants [22]; in some cases, we can find thorns or tough leaves [32].…”
Section: Freshwater and Continental Environmentsmentioning
confidence: 99%
“…Structural defenses are more commonly found among upland plants than wetland plants [22]; in some cases, we can find thorns or tough leaves [32]. Chemical defenses are more widespread in macrophytes [23,31] as well as in various algae, cyanobacteria [22].…”
Section: Freshwater and Continental Environmentsmentioning
confidence: 99%
See 1 more Smart Citation